Validation of a Digital Work Simulation to Assess Machiavellianism and Compliant Behavior - Dubbelt, Lonneke (Journal of business ethics, 2015)
”This paper describes a new and innovative measure that is developed to predict workplace deviance through the measurement of Machiavellianism and Compliant Behavior. Two field studies were conducted to study the validity of the digital work simulation. In Study 1, (N = 113) support was found for the construct validity of the simulation. The constructs as measured with the simulation correlated significantly with self-reported measures of the constructs and were related to personality and self-esteem. Study 2 (N = 285) examined the criterion-related validity of the simulation and showed that through the assessment of Machiavellianism the simulation was able to predict workplace deviance, and incrementally predicted organizational deviance over and above the Machiavellianism Personality Scale. Machiavellianism as measured with the simulation was less susceptible to social desirable answering compared to the Machiavellianism self-report. The paper finishes with study limitations, future research directions, and practical implications.